2021
DOI: 10.1126/sciadv.abe5518
|View full text |Cite
|
Sign up to set email alerts
|

The deacetylation-phosphorylation regulation of SIRT2-SMC1A axis as a mechanism of antimitotic catastrophe in early tumorigenesis

Abstract: Improper distribution of chromosomes during mitosis can contribute to malignant transformation. Higher eukaryotes have evolved a mitotic catastrophe mechanism for eliminating mitosis-incompetent cells; however, the signaling cascade and its epigenetic regulation are poorly understood. Our analyses of human cancerous tissue revealed that the NAD-dependent deacetylase SIRT2 is up-regulated in early-stage carcinomas of various organs. Mass spectrometry analysis revealed that SIRT2 interacts with and deacetylates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Our laboratory also explored additional functions of NPCs beyond nuclear transport [14,15] and found that nucleoporins Rae1 [16,17], Tpr [18][19][20], Nup358/RanBP2 [21], Nup62 [22], Nup58 [23], and Nup88 [24] play critical roles in maintaining spindle bipolarity, centrosome and mid-body homeostasis during cell division [25,26]. For instance, we provided several lines of evidence that the phosphorylation of the cohesin subunit, SMC1, stimulates binding to mitotic Rae1 [27,28], a phenomenon recently confirmed by others to form part of a mechanism of antimitotic catastrophe in early tumorigenesis [29]. Indeed, Rae1 is highly overexpressed in colon cancer [30].…”
supporting
confidence: 75%
“…Our laboratory also explored additional functions of NPCs beyond nuclear transport [14,15] and found that nucleoporins Rae1 [16,17], Tpr [18][19][20], Nup358/RanBP2 [21], Nup62 [22], Nup58 [23], and Nup88 [24] play critical roles in maintaining spindle bipolarity, centrosome and mid-body homeostasis during cell division [25,26]. For instance, we provided several lines of evidence that the phosphorylation of the cohesin subunit, SMC1, stimulates binding to mitotic Rae1 [27,28], a phenomenon recently confirmed by others to form part of a mechanism of antimitotic catastrophe in early tumorigenesis [29]. Indeed, Rae1 is highly overexpressed in colon cancer [30].…”
supporting
confidence: 75%
“…Western blotting was performed as previously described (Yi et al, 2021). Cells or tissues were lysed with modified lysis buffer (150 mM NaCl, 1 mM NaF, 50 mM Tris-HCl (pH 7.6), 1 mM EDTA, 1 mM Na 3 VO 4 , 1% NP-40, 1 mM MgCl 2 , 1 mM DTT, 1 mM NaF, 0.25% sodium deoxycholate) containing protease inhibitor cocktail (Sigma) and 1 mM phenylmethylsulfonyl fluoride (PMSF) on ice and then subjected to a BCA assay (Pierce).…”
Section: Western Blot and Ip Analysesmentioning
confidence: 99%
“…As a member of class III histone deacetylates, SIRT2 catalyzes the nicotinamide adenine dinucleotide (NAD + )-dependent removal of acyl groups from lysine residues of substrates. SIRT2 is one of the key regulators of post-translational modifications of many proteins. , Aberrant activity of SIRT2 has been related to neurodegenerative diseases, cancer, and metabolic syndrome. , A growing body of evidence suggests that pharmacological modulation with SIRT2 inhibitors holds promise for cancer chemotherapy and chemoprevention. Triple-negative breast cancers (TNBCs), a subgroup of breast malignancies defined as cancers lacking the expression of estrogen receptor, progesterone receptor, and human epidermal growth factor receptor-2, represent highly invasive carcinomas with high metastatic potential, proneness to relapse, and poor prognosis . TNBCs have been frequently linked to SIRT2 overexpression .…”
Section: Introductionmentioning
confidence: 99%